Simultaneous care in oncology: Assessment of benefit in relation to symptoms, sex, and age in 753 patients - Galiano, Antonella; Schiavon, Stefania; Nardi, Mariateresa; Guglieri, Irene; Pambuku, Ardi; Martino, Rosalba; Bolshinsky, Maital; Murgioni, Sabina; Intini, Rossana; Soldà, Caterina; Marino, Dario; Daniel, Francesca; et al. (Frontiers in Oncology, 2022)
Background: Early activation of palliative care for patients with advanced cancer is central in the treatment trajectory. At the Veneto Institute of Oncology, a simultaneous-care outpatient clinic (SCOC) has been active since 2014, where patients are evaluated by an oncologist together with a palliative care team. Recently, we reported on consecutive patients admitted at SCOC from 2018 to 2021 in terms of appropriateness, process and outcome indicators. Here we report further analysis in the same group of 753 patients, evaluating other parameters and the correlation between symptom intensity, gender, age and survival. Methods: SCOC data were retrieved from a prospectively maintained database. Results: Female were 42.2%, median age was 68 years, with 46.7% of patients aged ≥70 years. Most prevalent disease type was gastrointestinal cancer (75.2%) and 90.9% of patients had metastatic disease. Median score for distress thermometer was 4; the vast majority of patients (98.6%) reporting physical problems, and 69.4% presenting emotional issues. Younger women demonstrated a significantly greater median distress than other patients (p=0.0018). Almost all symptoms had a higher prevalence on the 0-3 ESAS score, except for fatigue. Patients who received systemic anticancer treatment (SAT) in the last 60 days of life were 43.8%, 15.0% of whom received SAT in the last month and 3.1% in the last two weeks. For some symptoms females had more frequently ESAS >3. Pain and nausea were significantly less reported by older patients compared to younger adults. Male had a lower risk of having MUST score ≥ 2 (p=0.0311). Male and older patients showed a lower prognosis awareness (p=0.0011; p=0.0049 respectively). Older patients received less 30 days’ end-of-life SAT (p=0.0006) and had a death risk decreased by 20.0%. Conclusion: Our study identified two subgroups of patients with advanced cancer who require special attention and support due to important symptoms’ burden detected by PROMs tests: female and younger adults. These categories of patients require special attention and should be provided early access at SCOC. The role of oncologist remains crucial to intercept all patients in need of early palliative care, and balancing trade-offs of anticancer treatment in advanced metastatic disease.